Comment est abordée la question de l’innovation dans les sciences sociales ? - Jean Corneloup (Revue de Géographie Alpine)
Although innovation has today become a topical notion, given its fundamental importance in understanding the economy and the way our society adapts to its development goals, its characteristics and principles nevertheless need to be defined. While the 20th century was marked by important technological, political, economic and cultural changes, the current era seems to be increasingly bent on imposing innovation as a motor for the development of society. It is therefore important to understand how the question of innovation is currently being addressed, and in turn this involves looking at the different ways in which the innovative process is interpreted. Between the notional approach, which often remains vague and somewhat basic, and the theoretical approaches that attempt to present different perspectives for ways of understanding the innovation process, the path of knowledge is very often compartmentalized by the different scientific disciplines. In this paper, we will attempt to show the tensions and combinations that exist between the different approaches adopted by the management sciences, sociology, economics and geography in attempting to understand the innovative process. To do so, we will focus our study on the firm and the territory (as the spatial dimension of innovation), elements that have already been the subject of numerous studies to understand the forces participating in the production of novelty.